'A war of houses and a war of land': Gentrification, post-politics and resistance in authoritarian Cambodia. (August 2021) - Lawreniuk, Sabina
Post-war property reforms in transitional Cambodia plunged the country into new conflict: a war of land. Under the guise of 'beautification', 11% of the capital's residents have been displaced in under two decades in a wave of violent gentrification, enacted through forced eviction and dispossession. Mounting resistance shows signs of taking effect, however, evincing a turning point in state–society relations. Here, the government has trialled a new approach, moving from techniques of violent expropriation towards a conciliatory method, built on dialogue, consultation and negotiation. Responding to calls for more work on resistance to gentrification and success in the fight to stay put, in this paper, I investigate these claims, bringing the literatures on gentrification and post-politics to bear on the evictions crisis in Cambodia. Drawing on testimony of former residents and media analysis, I examine techniques of removal and resistance in a case study of the eviction and demolition of Cambodia's White Building (1963–2017). I argue that recent shifts are not an abandonment of the state's compulsion to expropriation, exclusion and expulsion but a subtle modification of its gentrification strategy: away from the naked coercion associated with its own kleptocratic variant of authoritarian neoliberalism towards the post-political manufacture of hollow consent.